Targeted health and social care interventions for women and infants who are disproportionately impacted by health inequalities in high-income countries: a systematic review - Zahra Khan; Zoe Vowles; Cristina Fernandez Turienzo; Zenab Barry; Lia Brigante; Soo Downe; Abigail Easter; Seeromanie Harding; Alison McFadden; Elsa Montgomery; Lesley Page; Hannah Rayment-Jones; et al. (BMC, 2023)
Abstract Background Disadvantaged populations (such as women from minority ethnic groups and those with social complexity) are at an increased risk of poor outcomes and experiences. Inequalities in health outcomes include preterm birth, maternal and perinatal morbidity and mortality, and poor-quality care. The impact of interventions is unclear for this population, in high-income countries (HIC). The review aimed to identify and evaluate the current evidence related to targeted health and social care service interventions in HICs which can improve health inequalities experienced by childbearing women and infants at disproportionate risk of poor outcomes and experiences. Methods Twelve databases searched for studies across all HICs, from any methodological design. The search concluded on 8/11/22. The inclusion criteria included interventions that targeted disadvantaged populations which provided a component of clinical care that differed from standard maternity care. Results Forty six index studies were included. Countries included Australia, Canada, Chile, Hong Kong, UK and USA. A narrative synthesis was undertaken, and results showed three intervention types: midwifery models of care, interdisciplinary care, and community-centred services. These intervention types have been delivered singularly but also in combination of each other demonstrating overlapping features. Overall, results show interventions had positive associations with primary (maternal, perinatal, and infant mortality) and secondary outcomes (experiences and satisfaction, antenatal care coverage, access to care, quality of care, mode of delivery, analgesia use in labour, preterm birth, low birth weight, breastfeeding, family planning, immunisations) however significance and impact vary. Midwifery models of care took an interpersonal and holistic approach as they focused on continuity of carer, home visiting, culturally and linguistically appropriate care and accessibility. Interdisciplinary care took a structural approach, to coordinate care for women requiring multi-agency health and social services. Community-centred services took a place-based approach with interventions that suited the need of its community and their norms. Conclusion Targeted interventions exist in HICs, but these vary according to the context and infrastructure of standard maternity care. Multi-interventional approaches could enhance a targeted approach for at risk populations, in particular combining midwifery models of care with community-centred approaches, to enhance accessibility, earlier engagement, and increased attendance. Trial registration PROSPERO Registration number: CRD42020218357.